2007
DOI: 10.1128/iai.02028-06
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Potential of Ehrlichia chaffeensis Strains of Distinct Genome Sequences

Abstract: Human monocytic ehrlichiosis, one of the most frequent life-threatening tick-borne zoonoses, is caused by Ehrlichia chaffeensis that lacks endotoxin and peptidoglycan. While sequence polymorphisms in several genes in E. chaffeensis strains have been reported, global genomic divergence and biological differences among strains are unknown. The objectives of the present study were to compare the genome sequences of strains of E. chaffeensis and to examine the virulence potentials of the strains with defined genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 53 publications
2
54
0
Order By: Relevance
“…The genes that vary between the two strains are more likely to encode virulence factors than the genes that are highly conserved between them. Our previous study of comparative genome hybridization showed genes varying among three E. chaffeensis strains of diverse virulence (36). Importantly, most of these genes encode putative membrane proteins and hypothetical proteins, suggesting a novel pathogenic mechanism.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The genes that vary between the two strains are more likely to encode virulence factors than the genes that are highly conserved between them. Our previous study of comparative genome hybridization showed genes varying among three E. chaffeensis strains of diverse virulence (36). Importantly, most of these genes encode putative membrane proteins and hypothetical proteins, suggesting a novel pathogenic mechanism.…”
mentioning
confidence: 99%
“…Dissection of the relative roles of the pathogen strain versus host factors is very difficult with human infections due to the relatively low number of clinical cases and laboratory tissue specimens with a full data set and unknowns regarding the strain type in most infections. The use of these three previously characterized E. chaffeensis strains (36) in a single experimental host species allows testing of whether there are intrinsic differences in the response to each strain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Arkansas and Wakulla strains of E. chaffeensis were propagated in DH82 cells as previously described (33). Antibodies used were rabbit anti-extracellular regulated kinase (anti-ERK) antibody, mouse anti-phosphorylated ERK monoclonal antibody (both from Cell Signaling, Danvers, MA), and mouse anti-tubulin monoclonal antibody (Santa Cruz, Santa Cruz, CA).…”
Section: Methodsmentioning
confidence: 99%
“…HME is caused by Ehrlichia chaffeensis, a monocyte-tropic obligatory intracellular bacterium (9). Previously, we demonstrated that the Wakulla strain is more virulent than the type strain Arkansas in mice with severe combined immunodeficiency (SCID mice) (33). The Wakulla strain of E. chaffeensis causes a fatal illness in SCID mice; the mice develop fulminant hepatitis and show upregulation of tumor necrosis factor alpha (TNF-␣) and interleukin-1␤ (IL-1␤), several chemokines, including CXCL2 (Mip2, a mouse homolog of human IL-8), and chemokine receptors in the inflammatory liver (32).…”
mentioning
confidence: 99%